LOCAL TOUR GUIDE COMPETENCE PERSPECTIVE IN SUPPORTING SERVICE PERFORMANCE IN SESAOT TOURISM VILLAGE - Baiq Wikartin Januarini; Surayyal Hizmi; Endang Sri Wahyuni (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2024)
Currently, there is no urgency in the context of Local Tour Guide competency which is the main concern in developing the quality of human resources, especially in one of the tourist destinations, namely the Sesaot tourist village. In several studies, it is stated that the level of competence has an important role as an indicator in supporting service performance in a tourism destination, but there has been no research regarding the perception of local tour guides regarding their competence. Therefore, this research raises this issue using a descriptive qualitative approach. The data in this research was obtained through a process of observation, interviews and documentation. Interviews were conducted with three informants from BUMDES, tourism awareness group (POKDARWIS) and local guides, where these three components influence the resource competency development program in the Sesaot tourist village. The data collection process was carried out for 3 months, followed by data analysis using the Creswell approach for qualitative research. Based on the results of observations and interviews, it was found that village administrators and local tour guides have the same view regarding the importance of competency certification for local guides and expect assistance from the government or related agencies in assisting local tour guide competency certification in supporting service performance in the Sesaot tourist village. However, the implementation of competency certification for tour guides has not been implemented due to minimal government support or suboptimal planning. Considering this, annual planning for increasing human resources in the Sesaot tourist village needs to be included in the village's annual planning